PENGARUH PENGGUNAAN MEDIA VISUAL PREZI TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SENI RUPA - Drs. Abd. Hafiz, M.Pd., Risa Arnova, Dra. Zubaidah, M.Pd., (Serupa The Journal of Art Education, 2017)
The purpose of this through to understand that there is an influence of using prezi visual media to the result of art at grade Junior High School 30 Padang. The kind of through that used is experiment interpretation score of pretest and posttest and then by technique interpretation encode for processing Random Sampling. This encode for processing collected by the test in the result of lesson. Finding in this through showing that : the result of student’s in the lesson by using prezi visual media is better, just than with students who teached without using a conventional media. That’s mean using prezi visual media needed to all of students for improving the result of students in the lesson specially for art in art at Junior High School 30 Padang.Keywords: Visual Media Prezi